2019
DOI: 10.1590/1519-6984.185417
|View full text |Cite
|
Sign up to set email alerts
|

Parasitoids diversity in organic Sweet Pepper (Capsicum annuum) associated with Basil (Ocimum basilicum) and Marigold (Tagetes erecta )

Abstract: The sweet pepper (Capsicum annuum L.) is one of the most important crops in Brazilian farming. Many insect are related to this crop, compromising the quantity and quality of the fruit, representing a production problem. Vegetable diversification is one of the main elements that can be managed for suppressing undesirable insect populations in organic production, once that supports the presence of natural enemies. The basil Ocimum basilicum L. and the marigold Tagetes erecta L. are attractive and nutritious plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 32 publications
0
16
1
3
Order By: Relevance
“…Bell pepper (Capsicum annuum L.), belonging to the solanaceous family, is considered one of the most cultivated vegetables in Brazil [11] occupying among the ten most important vegetables on the market, both in value and volume sold.…”
Section: Introductionmentioning
confidence: 99%
“…Bell pepper (Capsicum annuum L.), belonging to the solanaceous family, is considered one of the most cultivated vegetables in Brazil [11] occupying among the ten most important vegetables on the market, both in value and volume sold.…”
Section: Introductionmentioning
confidence: 99%
“…The marigold yellow color is an attraction for parasitoids to perch and suck the nectar. The shape and color of marigolds are the most ideal for parasitoids looking for food (Souza et al 2019). Several types of parasitoid Brassicaceae pests found inhabiting marigolds, for example, the Family Braconidae, Ichneumonidae, Eulophidae, and Pteromalidae (Velcheva et al 2017) and Tachinidae (Razmi et al 201).…”
Section: Discussionmentioning
confidence: 99%
“…It follows the research results reported by Putra & Utami (2020), who researched chili plants in Wiyoro Village, Banguntapan District, Bantul Regency, Yogyakarta Special Region. Souza et al (2019) investigated red chili plantations in Pakem District, Sleman Regency, Yogyakarta Special Region, that the three families are natural enemy insect families that dominate in chili plantations. Furthermore, Souza et al (2019) added that the diversity of natural enemy insects in chili plants is indeed low, namely that only a few species are found consisting of one family.…”
Section: Diversity Of Natural Enemy Insectsmentioning
confidence: 99%